Cascading effects of algal warming in a freshwater community. (2nd March 2021) - Tseng, Michelle; Di Filippo, Carla M.; Fung, Madeline; Kim, Jihyun O.; Forster, Ian P.; Zhou, Yilin
Abstract: Research on the effects of climate warming on ecological communities has focused on how temperature affects resource quantity. However, resource quality is also affected by warming, and changes in resource quality can have meaningful effects on the productivity of higher trophic levels. Aquatic communities in particular experience temperature‐mediated shifts in resource quality because the nutritional value of algae is highly sensitive to temperature. For example, the production of healthful omega‐3 polyunsaturated fatty acids (n‐3 PUFA) by algae often decreases with warming. Decreased levels of some algal PUFAs with warming have led to the hypothesis that global warming should lead to an overall decrease in productivity in aquatic communities. However, this hypothesis: (a) potentially oversimplifies the relationship between algal PUFAs and temperature, and (b) assumes that the nutritional requirements of consumers are not affected by temperature. Here, we test these assumptions using a freshwater community ( Scenedesmus algae, Daphnia zooplankton, Chaoborus insects). Warming temperatures increased total algal PUFAs, but decreased algal cell size, resulting in no net effect of temperature on PUFA per algal cell. In contrast, quantities of algal neutral lipids decreased with warming. At the consumer level, Daphnia fed 12°C‐reared algae maintained higher population sizes than those fed 20°C or 28°C‐reared algae. However, the effect of algal food type diminished as Daphnia rearing temperature increased. The indirect effects of cold‐reared algae on the growth rate of Chaoborus predators were minor. These data highlight the importance of investigating the effects of temperature on both resource quality and on the nutritional needs of consumers. Our results suggest that at warmer temperatures, consumer nutritional requirements may be reduced. We caution against broad claims that the negative relationship between some algal PUFAs and temperature should result in overall declines in aquatic productivity with ongoing climate warming. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.